Rāskāl - North, Sterling, 1906-1974.; Schoenherr, John; Muhammad, Ahmad Hasan; Abd al-Malik, Mushirah; Ibrahim, Dalya Muhammad (al-Qāhirah : Nahḍat Miṣr lil-Ṭibāʻah wa-al-Nashr wa-al-Tawzīʻ, 2005)
Novel.
P.B
P.B
Keywords: North, Sterling, -- 1906-1974 -- Childhood and youth -- Juvenile literature; North, Sterling, -- 1906-1974.; Authors, American -- 20th century -- Biography -- Juvenile literature; Rascal (Raccoon) -- Juvenile literature; Raccoon -- Wisconsin -- Biography -- Juvenile literature; Country life -- Wisconsin -- Juvenile literature; Raccoons; Country life -- Wisconsin; Écrivains américains -- 20e siècle -- Biographies -- Ouvrages pour la jeunesse; Rascal (Raton laveur) -- Ouvrages pour la jeunesse; Raton laveur -- Wisconsin -- Biographies -- Ouvrages pour la jeunesse; Authors, American; Country life; Raccoon; Rascal (Raccoon); Wisconsin; 1900-1999; Biographies; Juvenile works